La poetización de la añoranza en dos traducciones españolas del poema Matka de Julian Tuwim - Jackiewicz, Aleksandra (Romanica Silesiana)
The aim of the article is to present some of the translation difficulties that may arise while recreating the poetic idealization of nostalgia in the poem Matka by Julian Tuwim considered one of the most talented and renowned poets and translators of the period between the wars in Poland. The article focuses on the expressions that show profound links between the historical circumstances and personal experiences that are supposed to be an inspiration source for the author, and those that, in some cases, might be difficult to translate into Spanish, as well as may result from cultural and structural differences between the two languages. This comparative analysis is based on examples extracted from the Spanish translations of Julian Tuwim’s poem made by Maria Dembowska, Samuel Feijóo, Luis Melgarejo, and Joanna Studzińska. Key words: translation, poetry, nostalgia, reality, Julian Tuwim